Pay for performance for prenatal care and newborn health: evidence from a developing country - Alzúa, María Laura (2020)
Empirical literature analyzing the effect of pay-for-performance programs (P4P) for healthcare providers on maternal care and newborn health outcomes is scarce. In 2008, Uruguay’s Ministry of Public Health implemented a P4P called Metas Asistenciales (Healthcare Goals), a country-wide program that grants healthcare providers an economic incentive for complying with certain maternal and newborn healthcare goals. Health organizations use these funds to provide maternal and child health services. Using administrative records and a difference-in-difference methodology, we evaluate the effect of the Metas Asistenciales program on maternal and newborn health outcomes. We find that in the institutions affected by the program, 10 percentage points more women received an adequate number of prenatal checkups and pregnancy detection in the first trimester improved by 5 percentage points. We also found better results among newborns for indicators related to birth weight, premature births, and stillbirths. In sum, the program had a positive, significant impact on the rate of pregnant women’s utilization of health services and on newborn health outcomes. This study thus provides evidence supporting the idea that economic incentives are a promising tool for incentivizing healthcare providers to achieve better health services in developing countries.